Electrically pumped blue laser diodes with nanoporous bottom cladding - Sawicka, Marta; Muziol, Grzegorz; Fiuczek, Natalia; Hajdel, Mateusz; Siekacz, Marcin; Feduniewicz-Żmuda, Anna; Nowakowski-Szkudlarek, Krzesimir; Wolny, Paweł; Żak, Mikołaj; Turski, Henryk; Skierbiszewski, Czesław (Optics express, 2022)
We demonstrate electrically pumped III-nitride edge-emitting laser diodes (LDs) with nanoporous bottom cladding grown by plasma-assisted molecular beam epitaxy on c-plane (0001) GaN. After the epitaxy of the LD structure, highly doped 350 nm thick GaN:Si cladding layer with Si concentration of 6·10 19 cm -3 was electrochemically etched to obtain porosity of 15 ± 3% with pore size of 20 ± 9 nm. The devices with nanoporous bottom cladding are compared to the reference structures. The pulse mode operation was obtained at 448.7 nm with a slope efficiency (SE) of 0.2 W/A while the reference device without etched cladding layer was lasing at 457 nm with SE of 0.56 W/A. The design of the LDs with porous bottom cladding was modelled theoretically. Performed calculations allowed to choose the optimum porosity and thickness of the cladding needed for the desired optical mode confinement and reduced the risk of light leakage to the substrate and to the top-metal contact. This demonstration opens new possibilities for the fabrication of III-nitride LDs.